The paleobiolinguistics of domesticated manioc (Manihot esculenta) - Brown, Cecil H.; Clement, Charles Roland; Epps, Patience L.; Luedeling, Eike; Wichmann, Søren (Ethnobiology Letters, 2013)
Paleobiolinguistics is used to identify on maps where and when manioc (Manihot esculenta) developed importance for different prehistoric groups of Native Americans. This information indicates, among other things, that significant interest in manioc developed at least a millennium before a village-farming way of life became widespread in the New World. © 2013 Society of Ethnobiology.